2018
DOI: 10.1002/jlb.3a0718-251r
|View full text |Cite
|
Sign up to set email alerts
|

Mannan-binding lectin deficiency exacerbates sterile liver injury in mice through enhancing hepatic neutrophil recruitment

Abstract: Noninfectious liver injury, including the effects of drugs and diet, is a major cause of liver diseases worldwide. The innate inflammatory response to hepatocyte death plays a crucial role in the outcome of liver injury. Mannan-binding lectin (MBL) is a pattern recognition molecule of the innate immune system, which is primarily produced by liver. MBL deficiency occurs with high frequency in the population and is reported associated with predisposition to infectious diseases. We here observed that genetic MBL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…These results were consistent with our previous finding that exogenous MBL reduces the inflammatory cytokine production of monocytes in vitro [16]. Additionally, we and others found that MBL deficiency elevated the inflammatory cytokines production both in mice [19] and humans [18]. Furthermore, this finding could be explained by an early study suggesting that the binding of MBL to autologous cells is most likely to take place at inflammatory loci, where it rec-ognizes endogenous ligands and induces the release of antiinflammatory mediators [48].…”
Section: Mediators Of Inflammationsupporting
confidence: 94%
See 1 more Smart Citation
“…These results were consistent with our previous finding that exogenous MBL reduces the inflammatory cytokine production of monocytes in vitro [16]. Additionally, we and others found that MBL deficiency elevated the inflammatory cytokines production both in mice [19] and humans [18]. Furthermore, this finding could be explained by an early study suggesting that the binding of MBL to autologous cells is most likely to take place at inflammatory loci, where it rec-ognizes endogenous ligands and induces the release of antiinflammatory mediators [48].…”
Section: Mediators Of Inflammationsupporting
confidence: 94%
“…Indeed, monocyte-derived DC from individuals with MBL deficiency showed an enhanced proinflammatory cytokine production in response to microbial stimulation [18]. Recently, we demonstrated that MBL ablation in mice could exacerbate sterile liver inflammation [19]. The other in vivo study also found that injection of recombinant MBL in mice could regulate the host immune response [20].…”
Section: Introductionmentioning
confidence: 98%
“…Taken together, studies indicate that sMBL is capable of controlling the activity of NK cells and can act as an immune response regulator [93]. Therefore, sMBL is a pleiotropic immune modulator that can influence various cell types of innate and adaptive immunity [93,94].…”
Section: Smbl Regulates Cytokine Production and Cytotoxicity Of Nk Cellsmentioning
confidence: 98%
“…The mannose receptor functions in endocytosis and phagocytosis, and is deeply involved in immune homeostasis by scavenging unwanted mannoglycoproteins [18]. Mannan-binding lectin (mannose-binding lectin) participates in the innate immune system and is produced mainly by hepatocytes [24,25].…”
Section: Mannans: Biological Function and Role In Pathologymentioning
confidence: 99%
“…Among the other pattern recognition receptors, the mannose receptor is among the best-characterized C-type lectins. It binds mannosyl, fucosyl, or N-acetylglucosamine (GlcNAc)-glycoconjugate ligands on various bacteria, fungi, and parasites to mediate significant inflammatory responses [25]. The mannose receptor also helps to clear glycosylated endogenous ligands.…”
Section: Mannans: Biological Function and Role In Pathologymentioning
confidence: 99%